Synthetic methods part (iv) protecting groups - Spivey,AC; Andrews,BI (Annual Reports on the Progress of Chemistry Section B, 2000)
Another excellent and comprehensive "update" review of protecting group (PG) strategies in organic synthesis has appeared this year.1 Additionally, a substantially expanded and updated 3rd edition of the classic "Protective Groups in Organic Synthesis" has been published.2 An introductory text on protecting groups has also appeared.3.